New technique for the development of open CNC cell controller based on ISO 14649 and ISO 6983 - Latif, Kamran (2015)
The aim of modern Computer Numerical Control (CNC) is to be more flexible, interoperable, adoptable, open and intelligent. In the projection towards the development of the next generation of CNC systems, the problem of current International Standards Organization (ISO) data interface model (ISO 6983) limitations was encountered. A new ISO standard known as Standard for The Exchange of Product Data (STEP) or ISO 10303 was introduced to overcome the issues of current data interface model in Computer Aided Design (CAD)/Computer Aided Manufacturing (CAM) systems. After that successful implementation, the standard was further extended to implement the STEP features on the CNC by introducing a new standard known as STEP-Numeric Control (NC) or ISO 14649. The implementation of STEP-NC was firstly initiated on the commercial CNC units by In-Direct STEP-NC programming approach. However, that approach failed to enable all the features of modern CNC systems due to the translation of data from high to low level and vendor specifications dependency of the commercial CNC units. A new controller is need to be developed in order to overcome these issues. In this study a new cell controller has been developed based on Open Architecture Control (OAC) technology and Interpreted STEP-NC programming approach. The aim of the developed system is to provide new techniques for both ISO data interface models (14649 and 6983) interpretation, along with its graphical verification, execution, monitoring and report generation functionalities into the CNC core. The implied system is composed of ISO data interface models interpretation, 3D simulation, machine motion control, live video monitoring and automatic document generation modules. The system has also been validated through manufacturing of case study components. Corresponding experimental results verified the proposed technique with satisfactory outcomes.